Role of Radiofrequency (Votiva, InMode) in Pelvic Floor Restoration - Dayan, Erez (Plast Reconstr Surg Glob Open, 2019)
BACKGROUND: Postpartum pelvic floor disorders are estimated to impact 24% of women in the United States. This study describes the use of a radiofrequency device (Votiva, InMode) for postpartum pelvic floor restoration using an electrostimulator to objectively measure treatment effect. METHODS: A retrospective evaluation was conducted between April 2017 and May 2018 of consecutive patients undergoing vaginal radiofrequency treatment. Inclusion criteria were patients at least 6 weeks postvaginal delivery with symptoms of pelvic floor dysfunction. Resting pelvic floor muscle tone and maximal pelvic floor contraction were measured. RESULTS: Fifty women were included in the study with an average age of 32 (29–40) years old, average of 2.6 pregnancies, and 1.8 vaginal deliveries. Two patients were lost to follow-up and excluded. Three complete radiofrequency treatments were performed in 31/50 patients, whereas 19 patients received 1–2 treatments. There were no adverse events from the radiofrequency treatment. No changes were found in resting pelvic muscle tone after Votiva treatment [Wilks’ lambda = 0.98, F (1, 45) = 0.86, P = 0.36]. The quantity of treatments seemed to impact mean values of maximal pelvic floor contraction [F (1, 45) = 105.14, P < 0.001]. On the patient questionnaire, patients felt subjective improvement correlated to number of treatments. CONCLUSIONS: Radiofrequency is safe for the treatment of pelvic floor dysfunction. This study showed no changes in resting pelvic muscle tone but an improvement in maximal pelvic floor contraction. A prospective randomized study is being conducted to further evaluate the efficacy of this technology.